La gestion du transport urbain au prisme de la « décharge » à Yaoundé (Cameroun) - Hyacinthe Atangana Bamela (EchoGéo)
The ‘welfare state’ model prevailed in Cameroon for a long time, but the economic crisis of the 1990s called this into question. This prompted the state to ‘offload’ the management of urban transport. This has led to the fragmentation of transport services and has had a serious impact on urban mobility. To analyse these challenges, a mixed approach combining quantitative data from a questionnaire addressed to the population and vehicle drivers, and qualitative perspectives from interviews with administrative and municipal officials was used. The research highlights the current challenges of this disengagement in Yaoundé while examining the reforms undertaken by the state to improve the sector. The research also identifies obstacles to implementation and calls for a thorough assessment of the consequences of disengagement in order to propose solutions that could improve urban transport in Yaoundé.